Locked Nucleic Acid Hydrolysis Probes for the Specific Identification of Probiotic Strains Bifidobacterium animalis subsp. lactis DSM 15954 and Bi-07™ - Shehata, Hanan R.; Kiefer, Anthony; Morovic, Wesley; Newmaster, Steven G. (Frontiers in Microbiology, 2021)
Probiotic health benefits are now well-recognized to be strain specific. Probiotic strain characterization and identification is thus important in clinical research and in the probiotic industry. This is becoming especially important with reports of probiotic products failing to meet the declared strain content, potentially compromising their efficacy. Availability of reliable identification methods is essential for strain authentication during discovery, evaluation and commercialization of a probiotic strain. This study aims to develop identification methods for strains Bifidobacterium animalis subsp. lactis DSM 15954 and Bi-07™ (Bi-07) based on real-time PCR targeting single nucleotide polymorphisms (SNP). The SNPs were targeted by PCR assays with locked nucleic acid probes, which is a novel application in probiotic identification. The assays were then validated following the guidelines for validating qualitative real-time PCR assays. Each assay was evaluated for specificity against 22 non-target strains including closely related Bifidobacterium animalis subsp. lactis strains and were found to achieve 100% true positive and 0% false positive rates. To determine reaction sensitivity and efficiency, three standard curves were established for each strain. Reaction efficiency values were 86%, 91% and 90% (R square values > 0.99), and 87%, 84% and 86% (R square values > 0.98) for B. animalis subsp. lactis DSM 15954 and Bi-07 assays, respectively. The limit of detection was 5.0 picograms and 0.5 picograms of DNA for DSM 15954 and Bi-07 assays, respectively. Each assay was evaluated for accuracy using five samples tested at three different DNA concentrations and both assays proved to be highly repeatable and reproducible. Standard deviation of Cq values between two replicates was always below 1.38 and below 1.68 for DSM 15954 and Bi-07 assays, respectively. The assays proved to be applicable to mono-strain and multi-strain samples as well as for samples in various matrices of foods or dietary supplement ingredients. Overall, the methods demonstrated high specificity, sensitivity, efficiency and precision and broad applicability to sample, matrix and machine types. These methods facilitate strain level identification of the highly monophyletic strains B. animalis subsp. lactis DSM 15954 and Bi-07 to ensure probiotic efficacy and provide a strategy to identify other closely related probiotics organisms.